O95 Comprehensive evaluation of EMG and biopsy findings supported by computer simulations – Preliminary study. Issue 9 (September 2017) - Zalewska, Ewa; Kierdaszuk, Biruta; Szmidt-Salkowska, Elzbieta; Kaminska, Anna; Gawel, Malgorzata
Abstract : Objective: Muscle biopsy and electrodiagnostic examinations are considered to be the complementary methods for either morphology or electrical activity of muscle. Simulation studies may serve as a direct link between muscle morphology and recorded bioelectrical activity and indicate i.e. number and diameter of muscle fibers contributing to motor unit potential. The aim of the study was to compare the values of the fiber diameter obtained in muscle biopsy with fiber size approximated by MUP analysis. Material and methods: Data of EMG and biopsy from biceps brachii muscle collected for three patients with suspection of muscular disorders were analysed. Muscle fiber diameters were also determined by MUPs analysis using simulation method. Histograms of muscle fiber diameters from biopsy and MUPs analysis were compared. Results: The values of fiber diameters obtained using MUPs analysis were similar with these from muscle biopsy ( p < 0.05 ). Conclusion: Analysis of MUPs supported by computer simulations may reveal muscle fiber diameters values similar to the values measured in biopsy and therefore may help to evaluate muscle fiber diameter variability and may serve as a guide for choosing the most proper muscle for biopsy studies. It could be especially useful in cases with clinical suspicion of myopathy that lack of myopathic abnormalities in QEMG. Significance: Extending the amount of information available from EMG examinations.